The effects of culture on students' learning styles - Rosniah Mustaffa, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2006)
Most teaching instruction at tertiary level is given in an auditory and visual mode where students have to listen to lectures, class discussions and presentations besides reading texts. This would be quite taxing for students who are not strong in these two modes of learning. A study was conducted to find out whether the low proficient students of the Bachelor of Arts programme in English Language Studies (BA ELS) at Universiti Kebangsaan Malaysia could "stretch" or adapt to the visual and auditory learning styles by using the following tools in collecting data: The Perceptual Learning Style Preference questionnaire (PLSP), journal writing, projection chniques, and a semi- structured interview. Findings show that they had difficulties expanding their normal cultural learning styles, nameely tactile and kinesthetic, to cope and adapt to the visual and auditory styles. This is because they were acculturated to conventional classroom roles and norms. This can also be attributed to the cultural background where they have been educated in a comparatively traditional, hierarchical system. Since learning styles may not be malleable, teachers can enhance student learning by introducing them to various learning styles at a very young age because this study has shown that students have difficulties adjusting to new learning styles at a later age.